EXPERIENCE OF FOREIGN COUNTRIES IN LABOR MIGRATION. - Avazxonovna, Imomova Nozimaxon; Tolanboevna, Nematova Dilfuzakhon (International Journal of Psychosocial Rehabilitation, 2020)
This study provides extensive coverage of the social consequences of labor migration in Germany and Australia.The study examines the social problems caused by migration flows in countries such as Germany and Australia, and the factors influencing them. The study found that in addition to the social problems that lead to migration, there are also factors that cause social problems that occur even after the migration process has taken place. Including:- Diversity of migrants and social strata of the host country;- Differences between migrants and the cultures of the host country- Migrants and the diversity of religious views in the host country, etc.